Haemodynamics During Induction with Sevoflurane Versus Propofol Using Laryngeal Mask Airways in Forearm Orthopaedic Surgeries in Older Children - Tooba Iqbal, Muhammad Shafiq, Muhammad Ali,Muhammad Imran Butt, Muhammad Nabeel (Journal of Rawalpindi Medical College, 2018)
Background: To compare the hemodynamic changes during induction of anesthesia with propofol and sevoflurane in children undergoing forearm orthopedic surgeries. Methods: In this descriptive study 60 pediatric patients, scheduled for forearm orthopedic surgical procedure under general anesthesia requiring LMA insertion were included. The selected patients were allocated into two groups; A (Propofol) and B (Sevoflurane) of 30 each. Group A was induced with IV Propofol 2mg/kg while Group B was induced by sevoflurane 6-8%. Anesthetic induction was supposedly achieved after loss of eyelash reflex. Results: Compared with base line, both groups showed a statistically significant decline in mean arterial pressure after induction. Propofol group (A) showed a larger transient decrease in MAP compared to sevoflurane group (B) (p<0.001). There was a statistical significant overall greater decline in MAP and heart rate after induction with propofol when compared with sevoflurane. Conclusion: Sevoflurane provides slightly better hemodynamic stability compared to propofol during anesthetic induction.